1998
DOI: 10.1001/archneur.55.4.500
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Lesion Analysis in Neurofibromatosis Type 1

Abstract: High-signal T2 lesions on MRI in patients with NF-1 evolve over time. The evolution of the NF-1 lesion is region specific and may relate to preferential region-specific effects of the NF-1 gene product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
4
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 13 publications
(14 reference statements)
6
44
4
2
Order By: Relevance
“…A similar pattern of evolution can be seen in Figures 2 and 4. Ramsby, 1998]. Despite this general agreement, we found a different and complex pattern of evolution of UBOs.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…A similar pattern of evolution can be seen in Figures 2 and 4. Ramsby, 1998]. Despite this general agreement, we found a different and complex pattern of evolution of UBOs.…”
Section: Discussionsupporting
confidence: 42%
“…These UBOs have been recognized as a distinctive feature of NF-1 since the late 1980s [Aoki et al, 1989;Goldstein et al, 1989;Mirowitz et al, 1989;Yamanouchi et al, 1995;North, 2000]. Cross-sectional analyses, and more recently longitudinal evaluations, indicate that UBOs tend to regress during adolescence [Itoh et al, 1994, DiMario andRamsby, 1998;North, 2000]. The first major serial study of UBOs included 13 subjects with two observations each, and assessed volume of UBOs in five locations: cerebral white matter, basal ganglia, brainstem, dentate nucleus, and cerebellar white matter [Itoh et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of these patients presented with symptoms referable to the brainstem and 4 were found incidentally on a screening MRI. DiMario and Ramsby [25] found that UBOs in the cerebellum and basal ganglia tend to decrease in number and size with increasing patient age, while brainstem UBOs demonstrated either no change or slight increase in size.…”
Section: Discussionmentioning
confidence: 99%